1980
DOI: 10.1073/pnas.77.4.2251
|View full text |Cite
|
Sign up to set email alerts
|

Studies on mechanism of action of anti-tumor-promoting agents: their specificity in two-stage promotion.

Abstract: The effects of fluocinolone acetonide (FA), retinoic acid (RA), and tosylphenylalanine chloromethyl ketone (TPCK) on two-stage promotion after 7,12-dimethylbenzfaJ anthracene (DMBA) initiation in female Sencar mice were investigated. The two-stage promotion protocol was achieved by twice weekly applications of 2 sg of 12Otetradecanoylphorbol 13-acetate (TPA) for 2 weeks (stage I) followed by twice Carcinogenesis in the skin can be induced by the sequential application of a subthreshold dose of a carcinogen (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
1
1

Year Published

1981
1981
2000
2000

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(55 citation statements)
references
References 9 publications
3
50
1
1
Order By: Relevance
“…Stage I promotion has also been directly shown to require DNA synthesis (Kinzel et al, 1984a). Taken together these studies indicate that epidermal hyperplasia or an event closely associated with it, is important for the completion of both stage I and stage II promotion, and this is supported by the work of Slaga et al (1980a) who reported that steroids [potent inhibitors of epidermal hyperplasia (Belman & Troll, 1972;Scribner & Slaga, 1973;Schwarz et al, 1977)] were potent inhibitors of both stage I and stage II promotion in SENCAR mice.…”
Section: Two-stage Epidermal Tumourigenesissupporting
confidence: 63%
See 3 more Smart Citations
“…Stage I promotion has also been directly shown to require DNA synthesis (Kinzel et al, 1984a). Taken together these studies indicate that epidermal hyperplasia or an event closely associated with it, is important for the completion of both stage I and stage II promotion, and this is supported by the work of Slaga et al (1980a) who reported that steroids [potent inhibitors of epidermal hyperplasia (Belman & Troll, 1972;Scribner & Slaga, 1973;Schwarz et al, 1977)] were potent inhibitors of both stage I and stage II promotion in SENCAR mice.…”
Section: Two-stage Epidermal Tumourigenesissupporting
confidence: 63%
“…Additional evidence that there are indeed two qualitatively different stages in promotion comes from the observations that the two stages are inhibited by different antagonists (Slaga et al, 1980a) and are dependent to different extents on the synthesis of prostaglandins F2a and E2 (Fustenberger & Marks, personal communication). This suggests that the two stages have a different molecular basis.…”
Section: Heterogeneity Of the Reponse Of Basal Keratinocytes To Tpa-imentioning
confidence: 99%
See 2 more Smart Citations
“…If there is indeed an irreversible cellular effect which can be produced by brief promotion, the simple dichotomy between normal cells and initiated cells will need to be extended to allow various categories of initiated cells (or microscopic clones of cells), and promotion itself may prove to be a multi-step process, as was suggested by Boutwell (1964) and Slaga et al (1980). Initiation w)ith promotion…”
Section: Resultsmentioning
confidence: 99%